A map of the knowledge bases for the chemical industry. (17th September 2007) - Mendonca, Joana; Baptista, Rui; Conde, Paulo
This paper examines the innovation processes in the chemical industry, by exploring the innovative activities undertaken by a Portuguese branch of a multinational chemical company. The paper presents a descriptive analysis of the company's formal innovation process. This research leads to a map of the knowledge bases, which allows for the identification of the company's underlying technologies and the knowledge flows. The map shows that the chemical industry is based on widely distributed knowledge bases, and that the main knowledge flows established with the surrounding environment are of the embodied form. In addition, this research shows that the ability to generate value-creating knowledge is concentrated in the early stages of the industry's life cycle, whereas the corresponding Portuguese industry is mostly concentrated on activities that have reached maturity and, in some cases, decline. Owing to this asymmetry, disembodied knowledge flows are difficult to create, and other types of relationship should be pursued.